Gold, Skin, and Body: Chinese Buddha Statues Are Constantly Being Shaped and Stripped - Liu, Xiangyu (Religions, 2023)
The brilliant effect of the Buddha not only strengthens Buddhist believers’ psychological effects of worship, consecration, and showing off of merits, but also becomes an important dissemination method to attract the public to join in. Starting from the golden skin of ancient Buddha statues, this paper analyzes the relevant historical documents and unearthed objects of gilded Buddha statues in ancient India, Afghanistan, Pakistan, and China and pays attention to the body decoration and technology dissemination as well as the process and influence of Chinese localization. In traditional Buddhist culture, gold technology and its application have an important impact on artistic expression, appearance protection, and the psychology of Buddhist statues. In the Late Tang Dynasty, the government and Buddhism suffered conflicts between supply and demand due to gold resources. The forced stripping of gilded Buddha statues became a historical epitome reflecting the deep social and economic problems.